Characteristics of a quasi-stationary non-self-sustained pulsed gas discharge with a hot cathode. (October 2015) - Borisov, D P; Kuznetsov, V M; Slabodchikov, V A
Abstract: The paper presents the electrode system and main characteristics of a non-selfsustained pulsed discharge with a hot cathode operating in argon at a pulse repetition frequency of 5 kHz and pulse duration of 50 ps. It is found that during the operation at a pressure of 0.3 Pa, the discharge current can reach amplitudes of up to 300 A and more with a rather high average discharge current of ∼ 100 A and low average discharge operating voltage of less than 20 V. The ion current from the discharge plasma to a Langmuir probe oscillates at frequency of about 100 kHz.